Acoustic feedback cancellation in hearing aids using dual adaptive filtering and gain-controlled probe signal. (July 2019) - Akhtar, Muhammad Tahir; Albu, Felix; Nishihara, Akinori
Highlights: A probe signal-based method for acoustic feedback cancellation in hearing aids. The proposed method comprises two adaptive filters working in tandem. A strategy is devised to transfer the coefficients between the two adaptive filters. The level of injected probe noise is automatically controlled by a gain parameter. Abstract: In this paper, we propose a probe signal-based adaptive filtering method for acoustic feedback cancellation (AFC) in hearing aids. The proposed method consists of two adaptive filters. The first adaptive filter is excited by the receiver (loudspeaker) signal, and uses the microphone signal as its desired response. The first adaptive filter shows a fast convergence speed, however, it may converge to a biased solution at the steady-state because its input and desired response are correlated with each other. The second adaptive filter is excited by an internally generated (uncorrelated) probe signal. The two adaptive filters are adapted using a delay-based normalized least mean square (NLMS) algorithm. A strategy is devised to exchange the coefficients of two adaptive filters such that the both adaptive filters give a good (unbiased) estimate of the acoustic feedback path. Furthermore, we propose to vary the gain of the probe signal, such that a high level probe signal is injected during the transient state, and a low level probe signal is used after the AFC system has converged. The computer simulations demonstrate that the proposed method achieves good modeling accuracy, preserves good speech quality, and maintains high output SNR at the steady-state.